Peningkatan Keterampilan Komunikasi dengan Metode Pembelajaran Role Playing pada Siswa Kelas V Sekolah Dasar - Adysa Alkhamdah Kurniasari; Arya Setya Nugroho; Nanang Khoirul Umam; Nataria Wahyuning Subayani (Journal on Education, 2023)
Based on the findings of observations, it was determined that students in class V still lacked adequate communication skills. It was found that only 50% of students saw the other person when communicating, 50% of students with a clear voice when speaking, 40% of students used good grammar, 40% of students with mastery of material content, and 45% of students who used gestures and facial expressions as communication aids. This study aims to address the issue of students' verbal and nonverbal communication skills in class V UPT SD Negeri 51 Gresik in order to apply the role-playing method to social studies learning. Class Action Research Method (CAR). The steps taken to conduct this research were divided into four stages: planning, action, observation, and reflection. The method of collecting data in this study is observing teacher activities, observing student activities, and observing students' communication skills. According to the findings of this study's analysis, using the role-playing technique enables students to develop effective communication with teachers and their peers. Then in the implementation of role playing or doing role play, students are more active and responsive from the beginning to the end of learning. Thus the role playing method to improve students' communication skills is declared effective.